Liberia : Agriculture Sector Public Expenditure Review - World Bank (Washington, DC, 2014)
This basic Agriculture Public Expenditure Review (AgPER) documents and analyzes information on the volume and structure of Liberia's past public expenditure on the agriculture sector and draws conclusions that can provide an orientation for future policies in view of the effectiveness of spending. The AgPER's focus is on the sectors of agriculture, including crops, fisheries, and forestry, in line with the New Partnership for African Development's (NEPAD) definition of the sectors of focus. This is in accordance with the Maputo Declaration and its target that governments devote ten percent of public expenditure for agricultural development with an aim towards realizing food security and poverty reduction.